EFEKTIFITAS TASK ANALYSIS DALAM MENINGKATKAN KEMAMPUAN MAKAN BAGI ANAK DOWN SYNDROME KELAS I C1 SLB FAN REDHA PADANG - Neldita Sonya (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstrack: Research early from problems which is the ability  to eat find at class of 1 CI SLB Fan Redha Padang, in subject specially the ability to eat. On building self-esteem, especially aspects of eating . When children eat lunch at school , children are often fed by parents , teachers and friends of children, so that children always rely on those who are nearby in the activities of the child's independence. So we need a method to solve this problems, one of them is of Task Analysis.This research use experiment type with single subject and A-B design. Subject of this Research is a student at class of 1 CI SLB Fan Redha Padang. Data’s collecting in the form of deed tes through perception/observation, and data collecting appliance in the form of instrument  tes counted 15 item. Acquirement of data analysed to use analyse visual data technique. Kata kunci: Task Analysis; Kemampuan Makan; Down Syndrome.